The influence of chalk grasslands on butterfly phenology and ecology. Issue 21 (7th October 2021) - Greenwell, Matthew P.; Botham, Marc S.; Bruford, Michael W.; Day, John C.; Evans, Luke C.; Gibbs, Melanie; Middlebrook, Ian; Roy, David B.; Watts, Kevin; Oliver, Tom H.
Abstract: The influence of large‐scale variables such as climate change on phenology has received a great deal of research attention. However, local environmental factors also play a key role in determining the timing of species life cycles. Using the meadow brown butterfly Maniola jurtina as an example, we investigate how a specific habitat type, lowland calcareous grassland, can affect the timing of flight dates. Although protracted flight periods have previously been reported in populations on chalk grassland sites in the south of England, no attempt has yet been made to quantify this at a national level, or to assess links with population genetics and drought tolerance. Using data from 539 sites across the UK, these differences in phenology are quantified, and M .  jurtina phenology is found to be strongly associated with both site geology and topography, independent of levels of abundance. Further investigation into aspects of M .  jurtina ecology at a subset of sites finds no genetic structuring or drought tolerance associated with these same site conditions. Abstract : Maniola jurtina phenology is found to be strongly associated with both site geology and topography, independent of mean abundance across 539 monitoring sites. Across a subset of sites, no genetic structuring was associated with these site characteristics. Populations displayed high levels of genetic diversity but low genetic differentiation. Across a subset of sites, drought tolerance was not associated with site geology.